Comparison of admitting neutrophil/lymphocyte ratio with baseline NIH stroke scale score in discriminating poor 30-day stroke outcome among Nigerian Africans - Olalusi, Oladotun V.; Yaria, Joseph; Makanjuola, Akintomiwa; Akinyemi, Rufus; Owolabi, Mayowa; Ogunniyi, Adesola (Frontiers in Stroke, 2025)
AimThe National Institutes of Health Stroke Scale (NIHSS) score is an established marker of stroke severity. Its use is time-consuming and requires formal training for optimal results. In contrast, the neutrophil-lymphocyte ratio (NLR), known to be independently associated with stroke outcome, can be readily calculated from routine peripheral blood counts with minimal training. We hypothesized that the NLR may perform similarly to the NIHSS score, in discriminating persons with poor 30-day stroke outcome, in a low-resource setting.MethodsWe followed up 106 participants with clinico-radiologic diagnosis of first-ever acute ischemic stroke (AIS). Patients with clinico-laboratory features of fever, aspiration pneumonia, sepsis, or infection were excluded at baseline. The NLR was obtained at admission while the functional outcome was assessed using the modified Rankin scale (mRS) score at day 30. Receiver operating characteristics (ROC) curves and Cox proportional hazards were used to determine the discriminatory ability of the NLR compared with the NIHSS score in identifying patients with poor 30-day stroke outcome (mRS > 3). The respective areas under the curves (AUC) and HRs (95%CI) were documented.ResultsThe median interquartile range (IQR) NLR of the study population was 2.87 (3.0). Patients in the higher tertiles of NLR had higher mean standard deviation 30-day mRS scores of 4.9 (1.2) compared to the middle 3.3 (1.2) and lower tertiles 2.3 (1.2) (p < 0.001). Admitting NLR had an AUC (95% CI) of 0.83 (0.75–0.91) and HR (95%CI) of 1.19 (1.01–1.40) compared to admitting NIHSS score with AUC of 0.89 (0.84–0.95) and HR of 1.25 (1.14–1.37) in discriminating poor 30-day outcome.ConclusionThe NLR alone performed similarly to the NIHSS score and may help identify patients with adverse 30-day AIS outcome in low-resource settings.